Analysis of Information Needs for the Establishment of a Supply Management System for Waste Groups in Poland - Kowalski, Jakub; Krzos, Grzegorz (Identyfikacja potencjału podaży grup odpadów w Polsce, 2024)
Aim: The aim of the research is to accurately present the current and future status of the availability of municipal waste for thermal conversion with energy recovery, and to determine the balance of the level of supply of this waste (alternative fuels) in the RP market in relation to the level of its processing in installations in Poland. Methodology: To conduct the study, the desk research method was used, which involves an evaluation of the records of available data sources, particularly their compilation, peer review and processing. Four publicly available, up-to-date documents and studies were used for this purpose. Results: The research fulfilled the goal of presenting the state of availability of municipal waste for thermal conversion and the balance of its supply and processing in Poland. In 2022, the volume of municipal waste amounted to 13,420 thousand tons, and forecasts indicate a further increase until 2030. The analysis showed that in 2021 the stream of alternative fuels (RDF) exceeded the capacity for processing, suggesting the need for new investments. Efficient thermal conversion of waste is being implemented in Podlaskie, Zachodniopomorskie i Małopolskie provinces, and the cement industry is replacing coal with alternative fuels, exceeding the EU average by more than 60%. Implications and recommendations: The work indicates the need for further monitoring and analysis of the municipal waste market for thermal conversion in Poland. It also recommends the development and modernization of existing waste processing facilities to effectively use available alternative fuels for energy production. Further studies should also consider more spatial information, such as housing characteristics, the average income of households, environmental values, the psychological factors that influence the behaviour of the inhabitants, and the location of a municipality regarding metropolises and regional peripheries. Originality/value: The research is distinguished by its comprehensive approach to analysing the market for municipal waste for thermal conversion in Poland. The value of the work lies in the use of up-to-date, publicly available data sources and a detailed analysis of the balance of waste supply and processing, which provides valuable information for further research and activities in this area.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 45-54
Keywords: municipal waste; thermal conversion; alternative fuels; supply balance; waste market; odpady komunalne; przekształcanie termiczne; paliwa alternatywne; bilans podaży; rynek odpadów